The Effects of Language Shift and the Attraction for the Young Generation of Language Maintenance of Timorese West Amarasi Society in Jakarta - zafanya, Angelica; Ramadhina, Retno; Isminarni, Siti (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The objective of this study is to identify how language shift influences the attraction of the young generation to language maintenance in the West Amarasi Society in Jakarta. Mixed method research, which blends qualitative and quantitative approaches, is applied in this work. The researcher computes and examines data on language maintenance of the Timorese language in the community in Jakarta and language shift. The author breaks out data on the elements resulting from language shift, language maintenance, and societal shifts, together with the findings of interviews. Through sociolinguistic evaluation of Jakarta's west amarasi community, the study focuses on how language transmits language shift in this object